Elaborations and denials in children’s responses to yes-no any/some questions in forensic interviews - Szojka, Zsofia A. (Child maltreatment, 2023)
This study examined 379 4- to 12-year-old children’s answers to any/some and other yes-no questions in forensic interviews about sexual abuse (N = 10,041). Yes-no questions that include the terms any/some (e.g., "Did he say anything?") often implicitly ask for elaboration when the answer is yes ("What did he say?"). However, children may give unelaborated responses to yes-no questions, fail to recognize implicit requests, and falsely respond "no." As predicted, children gave more wh- elaborations in response to any/some questions than other yes-no questions, but younger children elaborated less often than older children. Also as predicted, children responded "no" more often to any/some questions than to other yes-no questions, and more often to "any" than to "some" questions. "No" responses were also more common when children were asked potentially vague anything/something questions and else/other/different questions. The results highlight the potential risks of asking children any/some questions.